Lesson 3 - The Ear, the Listening Apparatus and Psychoacoustics / Lesson 3 - The Ear, the Listening Apparatus and Psychoacoustics - Πολίτης Διονύσιος (ΑΡΙΣΤΟΤΕΛΕΙΟ ΠΑΝΕΠΙΣΤΗΜΙΟ ΘΕΣΣΑΛΟΝΙΚΗΣ, 2016)
Lesson 3 - The Ear, the Listening Apparatus and Psychoacoustics